2021
DOI: 10.3389/fmicb.2021.749171
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-ENST00000421645 Upregulates Kank1 to Inhibit IFN-γ Expression and Promote T Cell Apoptosis in Neurosyphilis

Abstract: Long non-coding RNAs are involved in many infectious diseases. Our previous studies showed that lncRNA-ENST00000421645 expression is increased in T lymphocytes of neurosyphilis patients compared to healthy controls. However, whether lncRNA-ENST00000421645 has biological functions remains unclear. The current study was undertaken to understand the mechanism of lncRNA-ENST00000421645 in T lymphocyte function in neurosyphilis patients. The lncRNA-ENST00000421645 pull-down assay showed that lncRNA-ENST00000421645 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…It is therefore conceivable that KANK1 homozygous mutations in its regulatory sequence could be responsible for impaired tissue reformation and fibrosis characteristic of the third phase of cGVHD. In addition, since KANK1 function seems to be linked to the JAK pathway and has been shown to inhibit IFN-γ to promote T cell apoptosis further investigation to determine its validity as a drug target candidate for the treatment of cGVHD is warranted [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore conceivable that KANK1 homozygous mutations in its regulatory sequence could be responsible for impaired tissue reformation and fibrosis characteristic of the third phase of cGVHD. In addition, since KANK1 function seems to be linked to the JAK pathway and has been shown to inhibit IFN-γ to promote T cell apoptosis further investigation to determine its validity as a drug target candidate for the treatment of cGVHD is warranted [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs regulate the transcription of many different functional genes through histone acetylation, and therefore produce a variety of effects. And there have been numerous experiments demonstrating that lncRNAs are closely related to tumour cell proliferation and metastasis, macrophage polarization, and apoptosis during cellular senescence under this mechanism [ [74] , [75] , [76] ].…”
Section: Direct Interaction Of Lncrnas With Proteinsmentioning
confidence: 99%
“…Other studies have found that the number of Treg cells in the CSF is reduced such that they are not sufficient to inhibit T-cell-mediated inflammation and subsequent injury to the meninges, brain parenchyma, spinal cord, and other tissues (37). Recent studies have also found that lncRNA-ENST00000421645 promotes T-cell apoptosis in patients with neurosyphilis by mediating IFN-γ production through interaction with PCM1 protein (38). An additional study showed that T. pallidum can adhere to the host cell surface and capillary lining through mucopolysaccharide enzymes, which destroy mucopolysaccharide-rich blood vessels.…”
Section: Etiology and Pathogenesis (E)mentioning
confidence: 99%